ANALYSIS OF CHARACTER AND CHARACTERIZATION IN THE OLD MAN AND THE SEA A NOVEL BY ERNEST HEMINGWAY - SEVENTILOFA, I GUSTI NGURAH OCTOVA (GANEC SWARA, 2018)
This thesis is aimed at analyzing the intrinsic elements of “The Old Man and the Sea”; especially focusing on the character and characterization. The data are gathered through internet and library research. The method used in this thesis is the objective approach. This approach only focuses on the intrinsic elements of literary work. The research investigates the intrinsic elements; character and characterization by clarifying and analyzing them. And the data analyses are conducted in defining the characterization of characters and the types of characters